The effect of iron carboxymaltose treatment on quality of life in women with iron deficiency - Helvacıoğlu, Çağlar; Ekin, Murat (Journal of Surgery and Medicine, 2020)
Aim: Iron deficiency is the most common cause of anemia in over the world and affects 20% of women, even in developed countries. In this study, our aim is to calculate the change in the quality of life of patients treated with parenteral ferric carboxymaltose. Methods: In this retrospective cohort study, quality of life scores were evaluated before and after 6 weeks of treatment using the Short Form 36 scale. Fifty patients receiving parenteral ferric carboxymaltose treatment in Bakirkoy Dr. Sadi Konuk Training and Research Hospital, Department of Gynecology and Obstetrics were included. Results: Pretreatment ad posttreatment hemoglobin values were 8.22 g/dl and 12.02 g/dl, respectively. Pretreatment physical role functioning score was 34.7 (39) and it was calculated as 54.2 (39.8) after the treatment (P=0.006). There were no significant differences between pre- and post-treatment emotional strength, (P=0.330), energy vitality, (P=0.210), mental health (P=0.910) scores and sub-dimensions. Minor side effects were observed in 3 patients. Conclusion: Parenteral ferric carboxymaltose therapy significantly improves quality of life, especially physical role strength. Iron deficiency should be replaced effectively.